A Bibliometric Analysis of Cultural Change Management in HR - Loso Judijanto; Wahyudin Wahyudin (Westscience Press, 2026)
The current study performs a bibliometric investigation of the field of cultural change management in HRM and investigates its intellectual structure, the process of thematic evolution, and the global collaboration pattern. With the help of bibliometrics methods, the analysis of keywords co-occurrence, density visualization, citation impact, co-authorship network, and country level of collaboration is carried out. The results show that the concept of HRM represents the main hub of scientific research and is closely related to concepts of organizational culture, change management, HRM, knowledge management, and information systems. Thematic evolution shows the evolution of the scientific field from the fundamental research on HRM and knowledge management towards research on organizational behavior and organizational culture and more recent research on digital transformation in terms of artificial intelligence, HR analytics, and IT-enabled HRM. The citation analysis suggests that most influential papers combine various disciplines like healthcare, operations management, and organizational studies. Finally, the collaboration network shows that the UK and the USA are leaders in terms of scientific production, whereas Australia, Germany, and Netherlands are intermediators for other countries in the field.